In vivo cleavage specificity of Trypanosoma brucei editosome endonucleases. Issue 8 (21st February 2017) - Carnes, Jason; McDermott, Suzanne; Anupama, Atashi; Oliver, Brian G.; Sather, D. Noah; Stuart, Kenneth
Abstract: RNA editing is an essential post-transcriptional process that creates functional mitochondrial mRNAs in Kinetoplastids. Multiprotein editosomes catalyze pre-mRNA cleavage, uridine (U) insertion or deletion, and ligation as specified by guide RNAs. Three functionally and compositionally distinct editosomes differ by the mutually exclusive presence of the KREN1, KREN2 or KREN3 endonuclease and their associated partner proteins. Because endonuclease cleavage is a likely point of regulation for RNA editing, we elucidated endonuclease specificity in vivo . We used a mutant gamma ATP synthase allele (MGA) to circumvent the normal essentiality of the editing endonucleases, and created cell lines in which both alleles of one, two or all three of the endonucleases were deleted. Cells lacking multiple endonucleases had altered editosome sedimentation on glycerol gradients and substantial defects in overall editing. Deep sequencing analysis of RNAs from such cells revealed clear discrimination by editosomes between sites of deletion versus insertion editing and preferential but overlapping specificity for sites of insertion editing. Thus, endonuclease specificities in vivo are distinct but with some functional overlap. The overlapping specificities likely accommodate the more numerous sites of insertion versus deletion editing as editosomes collaborate to accurately edit thousands of distinct editing sites in vivo .